Assessment of permanent drift demands in steel moment-resisting steel buildings due to recorded near-fault forward directivity earthquake ground motions and velocity pulse models. (October 2020) - Ruiz-García, Jorge; Ramos-Cruz, José M.
Abstract: This paper presents the main results of an investigation focused on evaluating the height-wise distribution and amplitude of permanent interstorey drift, RIDR, demands of four case-study steel moment-resisting frames subjected to near-fault earthquake ground motions having forward-directivity effects (NF-FD) with increasing seismic intensity. To provide a context, maximum (transient) interstorey drift, IDR, demands were also computed as part of this study. Examining the results from nonlinear time-history analyses revealed that the case-study building models exhibited a recentering behaviour under NF-FD earthquake records, which means that the amplitude of RIDR at specific stories decreases with respect to the amplitude reached at a lower ground motion intensity. Scatter plots of maximum RIDR and IDR demands, and vice versa, revealed that both response parameters follow a nonlinear trend, which it can be approximated by a power funtion. Additionally, the ability of two velocity pulse analytical models introduced in the literature to estimate RIDR demands was also examined in this investigation. It was observed that both velocity pulse models lead to a different amplitude of RIDR demands computed from recorded earthquake ground motions; however, those equivalent pulses are adequate for estimating IDR drift demands as noted in previous studies.